2002
DOI: 10.1093/jac/dkf066
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of linezolid into bone, fat, muscle and haematoma of patients undergoing routine hip replacement

Abstract: Twelve patients undergoing total hip replacement were given 600 mg of linezolid as a 20 min iv infusion along with conventional prophylaxis of 1 g of cefamandole immediately before surgery. Routine total hip arthroplasty was carried out, and at timed intervals during surgery samples of bone, fat, muscle and blood were collected for assay by high-performance liquid chromatography analysis. Samples of the haematoma fluid that formed around the operation site and further blood samples for assay were also collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
84
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(92 citation statements)
references
References 10 publications
2
84
1
5
Order By: Relevance
“…In addition, the MSSA group was smaller, making statistical significance more difficult to achieve. The better outcomes among MRSA-infected patients also could be related to the enhanced skin and tissue penetration of linezolid (12,20,26,34) or to the inadequate dosing of vancomycin. The consensus on evidence-based guidelines for dosing vancomycin is poor (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MSSA group was smaller, making statistical significance more difficult to achieve. The better outcomes among MRSA-infected patients also could be related to the enhanced skin and tissue penetration of linezolid (12,20,26,34) or to the inadequate dosing of vancomycin. The consensus on evidence-based guidelines for dosing vancomycin is poor (43).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recent PK data for linezolid available in the literature focused on plasma concentrations (15), skin blister studies (8), and tissue biopsy specimens (14). Nevertheless, none of these techniques are capable of the assessment of the free concentrations of linezolid in tissues, which more accurately reflect the site of infection and drug action.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a previous study, the penetration efficacy of LZD into bone and muscle was 60 and 94%, respectively, at 20 min post-infusion. 4) Meanwhile, Komatsu et al reported LZD penetration efficacies of 88 and 84% into the bone marrow and iliopsoas muscles of rabbits, respectively, at 0.33 h post-injection. 33) Moreover, the LZD concentration was reported to be 1.6-fold higher in the cerebrospinal fluid than in the plasma of patients with central nervous system infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LZD is expected to maintain its therapeutic efficacy in tissues associated with poor blood flow (e.g., bronchoalveolar lavage, inflammatory fluid, bone, fat, muscle, and cerebrospinal fluid), making it an ideal option for treatment of deep-tissue infections. [2][3][4][5] Lastly, as the bioavailability of LZD is approximately 100%, 6) it is possible to switch from intravenous to oral administration while using the same dosage. Although these advantages make LZD an excellent antimicrobial agent, administration of LZD has been reported to cause adverse side effects such as gastrointestinal disturbances, thrombocytopenia, decreased hemoglobin/hematocrit levels, and cutaneous reactions.…”
mentioning
confidence: 99%